Class of Unbiased Integer GPS Ambiguity Estimators. - Teunissen, Peter (1998)
This contribution introduces a class of integer ambiguity estimators which are unbiased. The condition for unbiasedness is formulated and it is shown that this condition is satisfied for three ambiguity estimators which are often used in GPS ambiguity resolution. They are the 'rounding' estimator, the 'bootstrapped' estimator and the least-squares estimator. The geometry underlying these three integer estimators is discussed and compared.